The unsolved mystery of apoA-I recycling in adipocyte. Issue 1 (December 2016) - Wang, Shuai; Peng, Dao-quan; Yi, Yuhong
Abstract As the major storage site for triglycerides and free cholesterol, adipose tissue plays a central role in energy metabolism. ApoA-I is the main constituent of HDL and plays an important role in removal of excess cholesterol from peripheral tissues. Recently, multiple studies have shown beneficial effects of apoA-I on adipose metabolism and function. ApoA-I was reported to improve insulin sensitivity and exert anti-inflammatory, anti-obesity effect in animal studies. Interestingly, Uptake and resecretion of apoA-I by adipocytes has been detected. However, the significance of apoA-I recycling by adipocytes is still not clear. This article reviewed methods used to study cellular recycling of apoA-I and summarized the current knowledge on the mechanisms involved in apoA-I uptake by adipocytes. Since the main function of apoA-I is to mediate reverse cholesterol transport from peripheral tissues, the role of apoA-I internalization and re-secretion by adipocytes in intracellular cholesterol transport under physiological and pathological conditions were discussed. In addition, findings on the correlation between apoA-I recycling and obesity were discussed. Finally, it was proposed that during intracellular transport, apoA-I-protein complex may acquire cargoes other than lipids and deliver regulatory information when they were resecreted into the plasma. Although apoA-I recycling by adipocytes is still an unsolved mystery, it's likely that it is more than a redundant pathway especially under pathological conditions.